Optimization of the Samapta Patrol Unit Performance in Preventing the Illicit Circulation of Liquor in the Jurisdiction of Magetan Police - Putra, Aditya Dwi (Advances in Police Science Research Journal, 2024)
Implementation of patrols by the Magetan Police Samapta unit to prevent the illegal distribution of drinks hard is considered not optimal because it is not yet in the ideal position according to the governing rules. Starting from the condition of the organization’s resources, both in terms of quality and quantity lacking, patrol routes only go through frequently traveled roads so they are not diverse, implementation of patrols that are not in accordance with times that are prone to the distribution of alcohol, budget Fuel is not sufficient for patrol needs, and there is still a lack of public awareness about the dangers of consuming alcoholic beverages. Therefore, the implementation of patrols has been adjusted with the time and place where alcohol is often found in circulation, budget increases as well increasing the number of patrol personnel, and increasing the implementation of branch patrols in each police station.